An Adaptable Gamification Design in Online Education Based on the D6 Gamification Model - Özmen, Erhan; Kan, Ayşe Ülkü (My University, 2024)
The aim of this study is to present an adaptive gamification design in online education using the D6 gamification model and to guide researchers and gamification designers in the decision mechanisms that can be used in the gamification process of online systems. The study utilized a design-based research approach by using two iterative cycles during the development of the system. The initial gamification design was developed with the help of existing literature, and then this design was evaluated by a team of 14 people consisting of two software engineers, four educational sciences specialists, one graphic designer, one front end developer, two gamification specialists and four educational technologists selected by purposive sampling method. The design was also applied to a group of 14 female and 20 male students using the system. These students interacted with the system for two weeks and provided feedback in two one-week cycles. At the end of the two-week period, feedback from both experts and students showed that the usability of gamification can be maximized by improving and diversifying the content, increasing interaction, using reward mechanisms correctly, adapting the content for different age groups, including elements such as excitement and progression, encouraging participation with bonus points, balancing points with badges, ranking levels, using sound and time correctly, and designing a user-friendly interface.
Keywords: Online Learning; Gamification; Design-Based Research; Web Based Gamification System